Expansion and line-binned opacities of samarium ions for the analysis of early kilonova emission from neutron star mergers. Issue 1 (4th April 2023) - Carvajal Gallego, H; Deprince, J; Palmeri, P; Quinet, P
ABSTRACT: Opacity calculations performed within the expansion and the line-binned formalisms are reported for Sm V–X ions in this paper. These were determined by means of new large-scale atomic structure and radiative rate computations carried out using the pseudo-relativistic Hartree-Fock (HFR) method from which energy levels, wavelengths, and oscillator strengths were deduced for more than 100 millions of spectral lines in the considered samarium ions. In the absence of any experimental data, the reliability of HFR results was roughly estimated by comparison with those obtained with an independent theoretical approach, namely the fully relativistic multiconfiguration Dirac-Hartree-Fock method, in Sm VI and Sm VII. The opacities were estimated for typical conditions corresponding to early phases of kilonovae following neutron star mergers, i.e. for a density ρ  = 10 −10  g cm −3, a time after the merger t  = 0.1 day and temperatures ranging from 25 000 to 70 000 K. In addition, the atomic calculations allowed us to establish the ground level for each of the Sm ions considered (still unknown until now), as well as reliable partition functions that are crucial for the determination of the ionization balance by solving the Saha equation and for accurate opacity calculations.